Sulfur atom doped bimetallic catalyst and preparation method and application thereof
The bimetallic catalyst doped with sulfur atoms catalyzed the conversion of 5-hydroxymethylfurfural into 2,5-furandicarboxylic acid under mild conditions, solving the problem of high energy consumption of high temperature and high pressure or external O2 involved in the prior art. It has achieved efficient and environmentally friendly catalytic effects and has industrial application value.
Patent Information
- Application Number
- CN202411659131.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art requires high temperature and high pressure or external O2 to participate in catalyzing the conversion of 5-hydroxymethylfurfural into 2,5-furandicarboxylic acid, resulting in high energy consumption and no industrial application value.
Using sulfur atom-doped bimetallic catalyst, a hydrothermal reaction of noble metal compounds, soluble iron salts, sulfur sources and reducing agents in ethylene glycol, followed by annealing and calcining in air and H2/N2, can be prepared by A catalyst for efficient catalytic reaction under mild conditions.
It is achieved efficient conversion of 5-hydroxymethylfurfural into 2,5-furandicarboxylic acid under mild conditions, with a catalytic yield of 99%, and the catalyst has good cycle stability and is suitable for industrial production.
Smart Images

Figure CN119386900A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation, and in particular to a sulfur atom-doped bimetallic catalyst and a preparation method and application thereof. Background Art
[0002] Overexploitation and depletion of non-renewable fossil fuels have led to an intensified energy crisis and severe environmental pollution. Using renewable biomass resources to replace non-renewable fossil petroleum resources is a promising strategy that can not only reduce pollution emissions but also obtain high value-added chemicals. 5-Hydroxymethylfurfural (HMF) was selected by the U.S. Department of Energy as one of the top ten biomass-derived platform chemicals, and its derivatives can be used in fine chemicals, pharmaceutical intermediates, and agrochemicals. Aerobic oxidation of HMF to 2,5-furandicarboxylic acid (FDCA) is one of the key reactions involved in sustainable chemical processes based on biomass. HMF and FDCA play a vital role in renewable biomass chemistry and are considered to be the "sleeping giants" among bio-based intermediate chemicals. Compared with petroleum-based terephthalic acid, FDCA is a completely sustainable alternative and a major component of green polymers such as ethylene glycol 2,5-furandicarboxylate (PEF). Therefore, it is of great significance to achieve efficient conversion of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid under mild conditions.
[0003] In the past studies, the catalytic oxidation of HMF to FDCA mainly includes electrocatalysis, biocatalysis, photocatalysis, and thermal catalysis. Since the catalytic oxidation of HMF to FDCA involves multi-step selective oxidation, it is challenging to select a suitable catalyst. In the current research on the thermal catalytic oxidation of HMF to FDCA, it is often necessary to use higher temperature and oxygen pressure. CN118598832A discloses a method for preparing 2,5-furandicarboxylic acid by co-oxidation of 5-hydroxymethylfurfural. At 140°C, O is continuously introduced at a flow rate of 20 mL / min. 2 A 65% FDCA yield was obtained.
[0004] Most of the current methods require high temperature and high pressure or external O 2 The catalytic reaction is carried out without the participation of HMF, which greatly increases the energy consumption of the catalytic reaction. Therefore, it is very important to develop a method that can oxidize HMF to FDCA under mild conditions. Summary of the invention
[0005] The purpose of the present invention is to provide a sulfur atom-doped bimetallic catalyst and a preparation method and application thereof, which can efficiently convert 5-hydroxymethylfurfural into 2,5-furandicarboxylic acid under mild conditions and has excellent catalyst cycle stability.
[0006] To achieve the above object, the present invention provides a method for preparing a sulfur atom-doped bimetallic catalyst, comprising the following steps:
[0007] S1. Add the precious metal compound, the reducing agent, the soluble iron salt and the sulfur source to ethylene glycol, stir them thoroughly to dissolve them, transfer the mixed solution into a reactor for hydrothermal reaction, and after the reaction, centrifuge the obtained solid powder, wash it and put it into a vacuum oven for drying;
[0008] S2. The dried solid powder was placed in air and 10% H 2 / N 2 After annealing and calcination respectively, the sulfur atom-doped bimetallic catalyst was obtained.
[0009] Preferably, in step S1, the precious metal compound is one of chloroplatinic acid, ruthenium chloride, silver nitrate and chloroauric acid; the soluble iron salt is any one of ferric nitrate hydrate, ferric chloride hydrate or ferric sulfate hydrate, the sulfur source is one of thiourea, thioacetamide, cysteine and sulfur powder, and the reducing agent is one of sodium acetate or sodium citrate.
[0010] Preferably, in step S1, the molar ratio of the noble metal to iron is 0.0005-0.5; the molar ratio of sulfur to iron is 1-10, the molar ratio of the reducing agent to iron is 0.001-0.3, and the molar ratio of ethylene glycol to the added metal is 200-400.
[0011] Preferably, in step S1, the hydrothermal reaction time is 4-24 hours, and the hydrothermal reaction temperature is 100-300°C.
[0012] Preferably, in step S1, the washing reagent is anhydrous ethanol, the washing times are 2-20 times, and the drying temperature is 30-90°C.
[0013] Preferably, in step S2, the annealing temperature in air is 100-700°C, the holding time is 1-4h, and the heating rate is 3-9°C / min; 10% H 2 / N 2 The temperature of the intermediate annealing calcination is 50-200°C, the time is 30-120min, and the heating rate is 2-6°C / min.
[0014] The present invention also discloses a sulfur atom-doped bimetallic catalyst, wherein the chemical formula of the sulfur atom-doped bimetallic catalyst is M-FeO x S y , wherein M is any one of Pt, Ru, Ag and Au, and the noble metal supported catalyst is prepared by the above-mentioned preparation method of a sulfur atom-doped bimetallic catalyst.
[0015] The invention also discloses an application of a sulfur atom-doped bimetallic catalyst. The sulfur atom-doped bimetallic catalyst is applied to the preparation of 2,5-furandicarboxylic acid from 5-hydroxymethylfurfural.
[0016] Preferably, the method comprises the following steps:
[0017] The sulfur atom-doped bimetallic catalyst is added to a reaction bottle of 5-hydroxymethylfurfural solution, and sodium hydroxide is added, and then the reaction bottle is placed in a constant temperature reactor for oscillation reaction at 20-100° C. for 1-10 hours to obtain 2,5-furandicarboxylic acid;
[0018] Preferably, the concentration of the 5-hydroxymethylfurfural substrate solution is 0.1-3 mol / L, the amount of the noble metal supported catalyst added is 4-20 g / L, and the addition ratio of sodium hydroxide is 1-10 of the substrate molar ratio.
[0019] The present invention discloses a sulfur atom-doped bimetallic catalyst and a preparation method and application thereof, which have the following beneficial effects:
[0020] 1. M-FeO prepared by the present invention x S y The (M=Pt,Ru,Ag,Au) catalyst not only forms Fe-OS bonds with transition metals by introducing heteroatom S, effectively regulating the strong metal support effect, but also modifies the electronic structure of the noble metal M (M=Pt,Ru,Ag,Au), accelerating the electron transfer rate in the catalytic process, thereby accelerating the reaction rate;
[0021] 2. Catalyst M-FeO prepared by the present invention x S y (M=Pt,Ru,Ag,Au) exhibits excellent performance in the catalytic oxidation of 5-hydroxymethylfurfural to prepare 2,5-furandicarboxylic acid under mild conditions, with a catalytic yield of up to 99% and good cyclic stability; the overall preparation process of the catalyst is simple and the reaction conditions are mild, providing application value for the industrial production of 2,5-furandicarboxylic acid.
[0022] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Reaction route for the preparation of 2,5-furandicarboxylic acid from 5-hydroxymethylfurfural;
[0024] Figure 2 The Au-FeO prepared in Example 1 of the present invention x S y Scanning electron microscopy image of the catalyst. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0026] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0027] In addition, it should be understood that although this specification is described according to the implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. These other implementation modes are also covered within the protection scope of the present invention.
[0028] To achieve the above object, the present invention provides a method for preparing a sulfur atom-doped bimetallic catalyst, comprising the following steps:
[0029] S1. Add the precious metal compound, the reducing agent, the soluble iron salt and the sulfur source to ethylene glycol, stir them thoroughly to dissolve them, transfer the mixed solution into a reactor for hydrothermal reaction, and after the reaction, centrifuge the obtained solid powder, wash it and put it into a vacuum oven for drying;
[0030] S2. The dried solid powder was placed in air and 10% H 2 / N 2 After annealing and calcination respectively, the sulfur atom-doped bimetallic catalyst was obtained.
[0031] In step S1, the noble metal compound is chloroplatinic acid (H 2 PtCl 6 ), ruthenium chloride (RuCl 3 ), silver nitrate (AgNO 3 ), chloroauric acid (HAuCl 4 ); the soluble iron salt is any one of ferric nitrate hydrate, ferric chloride hydrate or ferric sulfate hydrate, the sulfur source is one of thiourea, thioacetamide, cysteine and sulfur powder, and the reducing agent is one of sodium acetate or sodium citrate.
[0032] In step S1, the molar ratio of precious metal to iron is 0.0005-0.5, preferably 0.01-0.3, and more preferably 0.03-0.2; the molar ratio of sulfur to iron is 1-10, preferably 2-8, and more preferably 3-7; the molar ratio of reducing agent to iron salt is 0.001-0.3, preferably 0.005-0.25, and more preferably 0.008-0.15; the molar ratio of ethylene glycol to added metal is 200-400, and preferably 250-350.
[0033] In step S1, the hydrothermal reaction time is 4-24 hours, preferably 6-20 hours, and more preferably 8-18 hours. The hydrothermal reaction temperature is 100-300°C, preferably 120-250°C, and more preferably 160-220°C.
[0034] In step S1, the washing agent is anhydrous ethanol, the washing times are 2-20 times, preferably 5-15 times, and more preferably 8-12 times. The drying temperature is 30-90°C, more preferably 40-80°C, and more preferably 50-70°C.
[0035] In step S2, the temperature of annealing and calcining in air is 100-700°C, preferably 200-600°C, and more preferably 300-500°C; the holding time is 1-4h, preferably 2-3h, and the heating rate is 3-9°C / min; more preferably 5-7°C / min;
[0036] 10% H 2 / N 2 The temperature of the intermediate annealing calcination is 80-200°C, more preferably 100-150°C; the calcination time is 30-120min, more preferably 60-100min, and the heating rate is preferably 2-6°C / min, more preferably 3-5°C / min.
[0037] The present invention also discloses a sulfur atom-doped bimetallic catalyst, the chemical formula of which is M-FeO x S y , wherein M is any one of Pt, Ru, Ag and Au, and the noble metal supported catalyst is prepared by the above-mentioned preparation method of a sulfur atom-doped bimetallic catalyst.
[0038] The present invention also discloses an application of a sulfur atom-doped bimetallic catalyst, wherein the sulfur atom-doped bimetallic catalyst is applied to the preparation of 2,5-furandicarboxylic acid from 5-hydroxymethylfurfural. The reaction route of preparing 2,5-furandicarboxylic acid from 5-hydroxymethylfurfural is as shown in the attached specification. Figure 1 shown.
[0039] The following steps are involved:
[0040] The sulfur atom-doped bimetallic catalyst is added to a reaction bottle of 5-hydroxymethylfurfural solution, and sodium hydroxide is added, and then the reaction bottle is placed in a constant temperature reactor for oscillation reaction at 20-100° C. for 1-10 hours to obtain 2,5-furandicarboxylic acid;
[0041] The concentration of the 5-hydroxymethylfurfural substrate solution is 0.1-3 mol / L, more preferably 0.2-2 mol / L. The amount of the noble metal supported catalyst added is 4-20 g / L, more preferably 8-16 g / L. The addition ratio of sodium hydroxide is 1-10 of the substrate molar ratio, preferably 2-8, more preferably 3-7.
[0042] After the reaction is completed, the yield of 2,5-furandicarboxylic acid obtained by the catalytic oxidation reaction of 5-hydroxymethylfurfural is determined by liquid chromatography.
[0043] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0044] Example 1
[0045] (1) 1 mol of ferric nitrate, 0.05 mol of chloroauric acid hydrate, 0.01 mol of sodium acetate, and 3 mol of thiourea were placed in a beaker containing 150 mL of ethylene glycol and stirred thoroughly to dissolve. Then, the mixture was transferred to a reactor and subjected to a hydrothermal reaction at 180° C. After the reaction, the obtained solid powder was washed 10 times with anhydrous ethanol and then dried in a vacuum oven at 60° C.
[0046] (2) The dried solid powder was annealed and calcined at 300 °C in air at a heating rate of 5 °C / min for 2 h, and then heated to 10% H 2 / N 2 Au-FeO was obtained by annealing and calcining at 100°C in an atmosphere with a heating rate of 3°C / min for 60 min. x S y The SEM image of the catalyst is shown in the attached manual. Figure 2 shown.
[0047] (3) Prepare 50 mg of Au-FeO x S y The catalyst was added into a reaction bottle containing 5 mL of 0.3 mmol 5-hydroxymethylfurfural solution, and 20 mg of sodium hydroxide was added. After shaking reaction at 60° C. for 4 h, the yield of 2,5-furandicarboxylic acid obtained by the catalytic oxidation reaction was measured to be 99%.
[0048] Comparative Example 1
[0049] The catalyst FeO was prepared according to the catalyst preparation method in Example 1. x S y The catalyst FeO was obtained by adding chloroauric acid only in the catalyst preparation process and keeping other conditions the same. x S yThe catalyst is added in the preparation process of 2,5-furandicarboxylic acid, and the conditions of catalytic oxidation are the same as those in Example 1. After the reaction is completed, the yield of 2,5-furandicarboxylic acid obtained by catalytic oxidation of 5-hydroxymethylfurfural is determined in liquid chromatography.
[0050] The results of the catalysts prepared in Example 1 and Comparative Example 1 in the preparation of 2,5-furandicarboxylic acid are compared as shown in Table 1:
[0051] Table 1
[0052] catalyst HMF conversion rate (%) FDCA yield (%) Example 1 <![CDATA[Au-FeO x S y ]]> 100 99 Comparative Example 1 <![CDATA[FeO x S y ]]> 100 10
[0053] The comparison results show that the catalyst prepared in Example 1 achieves a high conversion rate of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid, while the comparative example 1 without the addition of Au has only a 10% FDCA yield, indicating that Au plays an important role in the catalytic process.
[0054] Example 2
[0055] (1) 1 mol of ferric chloride, 0.1 mol of chloroplatinic acid hydrate, 0.008 mol of sodium citrate, and 3 mol of cysteine were placed in a beaker containing 110 mL of ethylene glycol and stirred thoroughly to dissolve. The mixture was then transferred to a reactor for hydrothermal reaction at 160° C. After the reaction, the obtained solid powder was washed 10 times with anhydrous ethanol and then dried in a vacuum oven at 50° C.
[0056] (2) The dried solid powder was annealed and calcined at 400 °C in air at a heating rate of 5 °C / min for 3 h, and then heated to 10% H 2 / N 2 Pt-FeO was obtained by annealing and calcining at 120°C in an atmosphere with a heating rate of 3°C / min for 70 min. x S y .
[0057] (3) 50 mg of the prepared Pt-FeO x S y The catalyst was added into a reaction bottle containing 5 mL of 0.3 mmol 5-hydroxymethylfurfural solution, and 20 mg of sodium hydroxide was added. After shaking reaction at 70° C. for 8 h, the yield of 2,5-furandicarboxylic acid obtained by the catalytic oxidation reaction was measured to be 93%.
[0058] Comparative Example 2
[0059] The catalyst was prepared according to the catalyst preparation method in Example 2, and the catalyst was added in the preparation process of 2,5-furandicarboxylic acid, except that sodium hydroxide was not added during the catalytic process, and the other catalytic oxidation conditions were the same as in Example 2. After the reaction was completed, the yield of 2,5-furandicarboxylic acid obtained by the catalytic oxidation reaction of 5-hydroxymethylfurfural was determined by liquid chromatography.
[0060] The results of the catalysts prepared in Example 2 and Comparative Example 2 in the preparation of 2,5-furandicarboxylic acid are compared as shown in Table 2:
[0061] Table 2
[0062] catalyst HMF conversion rate (%) FDCA yield (%) Example 2 <![CDATA[Pt-FeO x S y ]]> 100 93 Comparative Example 2 <![CDATA[Pt-FeO x S y ]]> 40 7
[0063] The comparison results show that, compared with Example 2 in which sodium hydroxide was added, Comparative Example 2 in the absence of sodium hydroxide only exhibited a 7% FDCA yield, indicating that the catalytic reaction needs to be carried out in an alkaline environment.
[0064] Example 3
[0065] (1) 1 mol of ferric sulfate, 0.1 mol of silver nitrate hydrate, 0.01 mol of sodium acetate, and 0.009 mol of sulfur powder were placed in a beaker containing 120 mL of ethylene glycol and stirred thoroughly to dissolve. Then, the mixture was transferred to a reactor and subjected to a hydrothermal reaction at 200° C. After the reaction, the obtained solid powder was washed 8 times with anhydrous ethanol and then dried in a vacuum oven at 60° C.
[0066] (2) The dried solid powder was annealed and calcined at 350°C in air at a heating rate of 5°C / min for 3 h, and then heated to 10% H 2 / N 2 Ag-FeO was obtained by annealing and calcining at 120°C in an atmosphere with a heating rate of 3°C / min for 70 min. x S y .
[0067] (3) Prepare 50 mg of Ag-FeO x S y The catalyst was added into a reaction bottle containing 5 mL of 0.3 mmol 5-hydroxymethylfurfural solution, and 20 mg of sodium hydroxide was added. After shaking reaction at 60° C. for 8 h, the yield of 2,5-furandicarboxylic acid obtained by the catalytic oxidation reaction was measured to be 95%.
[0068] Example 4
[0069] (1) 1 mol of ferric chloride, 0.12 mol of ruthenium chloride hydrate, 0.011 mol of sodium citrate, and 3 mol of thioacetamide were placed in a beaker containing 120 mL of ethylene glycol and stirred thoroughly to dissolve. The mixture was then transferred to a reactor for hydrothermal reaction at 200° C. After the reaction, the obtained solid powder was washed 8 times with anhydrous ethanol and then placed in a vacuum oven at 60° C. for drying.
[0070] (2) The dried solid powder was annealed and calcined at 450°C in air at a heating rate of 5°C / min for 3 h, and then heated to 10% H 2 / N 2 Ru-FeO was obtained by annealing and calcining at 130°C in an atmosphere with a heating rate of 3°C / min for 70 min. x S y .
[0071] (3) 50 mg of the prepared Ru-FeO x S y The catalyst was added into a reaction bottle containing 5 mL of 0.3 mmol 5-hydroxymethylfurfural solution, and 20 mg of sodium hydroxide was added. After shaking reaction at 80° C. for 7 h, the catalytic oxidation reaction was measured to obtain a yield of 94% of 2,5-furandicarboxylic acid.
[0072] Therefore, the present invention adopts the above-mentioned sulfur atom-doped bimetallic catalyst and its preparation method and application, which can efficiently convert 5-hydroxymethylfurfural into 2,5-furandicarboxylic acid under mild conditions and has excellent cycle stability.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a sulfur atom-doped bimetallic catalyst, characterized in that: The following steps are involved: S1. Add the precious metal compound, the reducing agent, the soluble iron salt and the sulfur source to ethylene glycol, stir them thoroughly to dissolve them, transfer the mixed solution into a reactor for hydrothermal reaction, and after the reaction, centrifuge the obtained solid powder, wash it and put it into a vacuum oven for drying; S2. The dried solid powder is annealed and calcined in air and 10% H2 / N2 to obtain a sulfur atom-doped bimetallic catalyst.
2. The method for preparing a sulfur atom-doped bimetallic catalyst according to claim 1, characterized in that: In step S1, the noble metal compound is one of chloroplatinic acid, ruthenium chloride, silver nitrate and chloroauric acid; the soluble iron salt is any one of ferric nitrate hydrate, ferric chloride hydrate or ferric sulfate hydrate, the sulfur source is one of thiourea, thioacetamide, cysteine and sulfur powder, and the reducing agent is one of sodium acetate or sodium citrate.
3. The method for preparing a sulfur atom-doped bimetallic catalyst according to claim 1, characterized in that: In step S1, the molar ratio of the noble metal to iron is 0.0005-0.5; the molar ratio of sulfur to iron is 1-10, the molar ratio of the reducing agent to iron is 0.001-0.3, and the molar ratio of ethylene glycol to the added metal is 200-400.
4. The method for preparing a sulfur atom-doped bimetallic catalyst according to claim 1, characterized in that: In step S1, the hydrothermal reaction time is 4-24 hours, and the hydrothermal reaction temperature is 100-300°C.
5. The method for preparing a sulfur atom-doped bimetallic catalyst according to claim 1, characterized in that: In step S1, the washing reagent is anhydrous ethanol, the washing times are 2-20 times, and the drying temperature is 30-90°C.
6. The method for preparing a sulfur atom-doped bimetallic catalyst according to claim 1, characterized in that: In step S2, the annealing temperature in air is 100-700°C, the holding time is 1-4h, and the heating rate is 3-9°C / min; the annealing temperature in 10% H2 / N2 is 50-200°C, the holding time is 30-120min, and the heating rate is 2-6°C / min.
7. A sulfur atom-doped bimetallic catalyst, characterized in that: The chemical formula of the sulfur-doped bimetallic catalyst is M-FeO x S y , wherein M is any one of Pt, Ru, Ag and Au, and the noble metal supported catalyst is prepared by the preparation method of a sulfur atom-doped bimetallic catalyst as described in any one of claims 1-6.
8. Use of the sulfur atom-doped bimetallic catalyst as claimed in claim 7, characterized in that: The sulfur atom-doped bimetallic catalyst is applied to the preparation of 2,5-furandicarboxylic acid from 5-hydroxymethylfurfural.
9. The use of a sulfur atom-doped bimetallic catalyst according to claim 8, characterized in that: The following steps are involved: The sulfur atom-doped bimetallic catalyst is added to a reaction bottle of 5-hydroxymethylfurfural solution, and sodium hydroxide is added, and then the reaction bottle is placed in a constant temperature reactor for oscillation reaction at 20-100° C. for 1-10 hours to obtain 2,5-furandicarboxylic acid; 10. The use of a sulfur atom-doped bimetallic catalyst according to claim 9, characterized in that: The concentration of the 5-hydroxymethylfurfural substrate solution is 0.1-3 mol / L, the addition amount of the noble metal supported catalyst is 4-20 g / L, and the molar ratio of the addition ratio of sodium hydroxide to the substrate is 1-10.